Discours écoféministes et droit de l'environnement : chassez le naturel ? - Romain Gosse (Criminocorpus)
Ecofeminist thoughts have emerged during the seventies, aiming at highlighting the joint domination on feminine gender and nature. Yet, developping at the same time, modern environmental law does not seem to have been influenced by these ideas. Also, contrary to the anglophone legal academic field, the french doctrine has not adressed this crossing – though ecofeminism has been generating a renewed interest over the last few years. Thus, this contribution would propose a few trails of possible convergence between some ecofeminist discourses and some distinctive features or trends of environmental law, which also show potential criticisms against this area of law.